Blockade of the CD47/SIRPα checkpoint axis potentiates the macrophage-mediated antitumor efficacy of tafasitamab. - Biedermann, Alexander; Patra-Kneuer, Maria; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Mangelberger-Eberl, Doris; Berges, Johannes; Kellner, Christian; Altmeyer, Sarah; Bittenbring, Jörg Thomas; Augsberger, Christian; Ilieva-Babinsky, Kristina; Haskamp, Stefan; et al. (Haematologica, 2024)
Macrophages are one of the key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD19 antibody tafasitamab, approved in combination with lenalidomide for the treatment of relapsed or refractory diffuse large B-cell lymphoma (DLBCL). However, antibody-dependent cellular phagocytosis (ADCP) in the tumor microenvironment can be counteracted by increased expression of the inhibitory receptor SIRPα on macrophages and its ligand, the immune checkpoint molecule CD47, on tumor cells. The aim of this study was to investigate the impact of the CD47-SIRPα axis on tafasitamab- mediated phagocytosis and explore the potential of anti-CD47 blockade to enhance its antitumor activity. Elevated expression of both SIRPα and CD47 was observed in DLBCL patient-derived lymph node biopsies compared to healthy control lymph nodes. CRISPR-mediated CD47 overexpression affected tafasitamab-mediated ADCP in vitro and increased expression of SIRPα on macrophages correlated with decreased ADCP activity of tafasitamab against DLBCL cell lines. A combination of tafasitamab and an anti-CD47 blocking antibody enhanced ADCP activity of in vitro-generated macrophages. Importantly, tafasitamab-mediated phagocytosis was elevated in combination with CD47 blockade using primary DLBCL cells and patient-derived lymphoma-associated macrophages in an autologous setting. Furthermore, lymphoma cells with low CD19 expression were efficiently eliminated by the combination treatment. Finally, combined treatment of tafasitamab and an anti-CD47 antibody resulted in enhanced tumor volume reduction and survival benefit in lymphoma xenograft mouse models. These findings provide evidence that CD47 blockade can enhance the phagocytic potential of tumor-targeting immunotherapies such as tafasitamab and suggest that there is value in exploring the combination in the clinic.
EVALuna2:569373

Cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways by CD101 - Wrage, Marius; Holland, Tim; Nüse, Björn; Kaltwasser, Johanna; Fröhlich, Jessica; Arnold, Harald; Gießler, Claudia; Flamann, Cindy; Bruns, Heiko; Berges, Johannes; Daniel, Christoph; Hoffmann, Markus; et al. (Mucosal Immunology, 2024)
T lymphocytes and myeloid cells express the immunoglobulin-like glycoprotein cluster of differentiation (CD)101, notably in the gut. Here, we investigated the cell-specific functions of CD101 during dextran sulfate sodium (DSS)-induced colitis and Salmonella enterica Typhimurium infection. Similar to conventional CD101−/− mice, animals with a regulatory T cell-specific Cd101 deletion developed more severe intestinal pathology than littermate controls in both models. While the accumulation of T helper 1 cytokines in a CD101-deficient environment entertained DSS-induced colitis, it impeded the replication of Salmonella as revealed by studying CD101−/− x interferon-g−/− mice. Moreover, CD101-expressing neutrophils were capable to restrain Salmonella infection in vitro and in vivo. Both cell-intrinsic and -extrinsic mechanisms of CD101 contributed to the control of bacterial growth and spreading. The CD101-dependent containment of Salmonella infection required the expression of Irg-1 and Nox2 and the production of itaconate and reactive oxygen species. The level of intestinal microbial antigens in the sera of inflammatory bowel disease patients correlated inversely with the expression of CD101 on myeloid cells, which is in line with the suppression of CD101 seen in mice following DSS application or Salmonella infection. Thus, depending on the experimental or clinical setting, CD101 helps to limit inflammatory insults or bacterial infections due to cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways.
CRIS-Team Scopus Importer:2024-07-19

Krüppel-like factor 2 controls IgA plasma cell compartmentalization and IgA responses - Wittner, Jens; Schulz, Sebastian; Steinmetz, Tobit; Berges, Johannes; Hauke, Manuela; Channell, William M.; Cunningham, Adam F.; Hauser, Anja E.; Hutloff, Andreas; Mielenz, Dirk; Jäck, Hans-Martin; Schuh, Wolfgang (Mucosal Immunology, 2022)
Krüppel-like factor 2 (KLF2) is a potent regulator of lymphocyte differentiation, activation and migration. However, its functional role in adaptive and humoral immunity remains elusive. Therefore, by using mice with a B cell-specific deletion of KLF2, we investigated plasma cell differentiation and antibody responses. We revealed that the deletion of KLF2 resulted in perturbed IgA plasma cell compartmentalization, characterized by the absence of IgA plasma cells in the bone marrow, their reductions in the spleen, the blood and the lamina propria of the colon and the small intestine, concomitant with their accumulation and retention in mesenteric lymph nodes and Peyer’s patches. Most intriguingly, secretory IgA in the intestinal lumen was almost absent, dimeric serum IgA was drastically reduced and antigen-specific IgA responses to soluble Salmonella flagellin were blunted in KLF2-deficient mice. Perturbance of IgA plasma cell localization was caused by deregulation of CCR9, Integrin chains αM, α4, β7, and sphingosine-1-phosphate receptors. Hence, KLF2 not only orchestrates the localization of IgA plasma cells by fine-tuning chemokine receptors and adhesion molecules but also controls IgA responses to Salmonella flagellin.
CRIS-Team Scopus Importer:2022-04-15

Transcriptomes of MPO-Deficient Patients with Generalized Pustular Psoriasis Reveals Expansion of CD4+ Cytotoxic T Cells and an Involvement of the Complement System - Haskamp, Stefan; Frey, Benjamin; Becker, Ina; Schulz-Kuhnt, Anja; Atreya, Imke; Berking, Carola; Pauli, David; Ekici, Arif Bülent; Berges, Johannes; Mößner, Rotraut; Wilsmann-Theis, Dagmar; Sticherling, Michael; et al. (Journal of Investigative Dermatology, 2022)
Generalized pustular psoriasis is a severe psoriatic subtype characterized by epidermal neutrophil infiltration. Although variants in IL36RN and MPO have been shown to affect immune cells, a systematic analysis of neutrophils and PBMC subsets and their differential gene expression dependent on MPO genotypes was not performed yet. We assessed the transcriptomes of MPO-deficient patients using single-cell RNA sequencing of PBMCs and RNA sequencing of neutrophils in a stable disease state. Cell-type annotation by multimodal reference mapping of single-cell RNA-sequencing data was verified by flow cytometry of surface and intracellular markers; the proportions of CD4+ cytotoxic T lymphocytes and other CD4+ effector cells were increased in generalized pustular psoriasis, whereas the frequencies of naïve CD4+ T cells were significantly lower. The expression of FGFBP2 marking CD4+ cytotoxic T lymphocytes and CD8+ effector memory T cells was elevated in patients with generalized pustular psoriasis with disease-contributing variants compared with that in noncarriers (P = 0.0015). In neutrophils, differentially expressed genes were significantly enriched in genes of the classical complement activation pathway. Future studies assessing affected cell types and pathways will show their contribution to generalized pustular psoriasis's pathogenesis and indicate whether findings can be transferred to the acute epidermal situation and whether depletion or inactivation of CD4+ cytotoxic T lymphocytes may be a reasonable therapeutic approach.
CRIS-Team Scopus Importer:2022-07-08